2021
DOI: 10.1007/s10803-021-05070-0
|View full text |Cite
|
Sign up to set email alerts
|

Parental Views of Families of Children with Autism Spectrum Disorder and Developmental Disorders During the COVID-19 Pandemic

Abstract: The COVID-19 pandemic, the infection caused by the novel coronavirus detected in December 2019 by World Health Organization (WHO), has detrimentally impacted human life in a variety of areas. Many concepts including outbreak, pandemic, and quarantine have been an inseparable part of our lives. This kind of dialectic change naturally affects persons with autism spectrum disorder (ASD) and developmental disorders (DD) and their families. The present study using a mixed-method evaluation aims to reveal the impact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
44
3
20

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(72 citation statements)
references
References 41 publications
5
44
3
20
Order By: Relevance
“…Similar to previous findings [11,15], parents reported negative effects such as unmet educational and behavioural needs along with feelings of social isolation for their children. However, contrary to this, Meral [16] reported positive outcomes for children and their families including perceived improvements in verbal behaviour and self-care skills. Parents also perceived low levels of family distress, with feelings of happiness and satisfaction with quality of life [16].…”
Section: Behavioural Outcomescontrasting
confidence: 63%
See 3 more Smart Citations
“…Similar to previous findings [11,15], parents reported negative effects such as unmet educational and behavioural needs along with feelings of social isolation for their children. However, contrary to this, Meral [16] reported positive outcomes for children and their families including perceived improvements in verbal behaviour and self-care skills. Parents also perceived low levels of family distress, with feelings of happiness and satisfaction with quality of life [16].…”
Section: Behavioural Outcomescontrasting
confidence: 63%
“…However, contrary to this, Meral [16] reported positive outcomes for children and their families including perceived improvements in verbal behaviour and self-care skills. Parents also perceived low levels of family distress, with feelings of happiness and satisfaction with quality of life [16]. These findings were similar to Di Renzo et al [11] o also reported mixed outcomes for children and their families during the pandemic.…”
Section: Behavioural Outcomescontrasting
confidence: 63%
See 2 more Smart Citations
“…This is supported by research that has found that caregivers of children with NDDs (including children on the autism spectrum) reported worsening of mental health as well as a heightened level of stress due to the pandemic (13,28,68). Based on the limited qualitative and mixed method research conducted among children on the autism spectrum and their families during the pandemic, including in the project's preliminary qualitative interview analysis, the inability to leave the house and the lack of personal space (e.g., "me time") were some of the common themes that have been mentioned by majority of the caregivers interviewed (54,55,67). However, the level of anxiety did not elevate significantly for these parents during the lockdown.…”
Section: Group Difference (Diagnosis × Lockdown)mentioning
confidence: 99%